DRAFT OPERATING GUIDELINES for the Protection of the Arctic Marine Environment (PAME) Working Group. - Protection of the Arctic Marine Environment (PAME) (Arctic Council Secretariat, 2001)
DRAFT OPERATING GUIDELINES for the Protection of the Arctic Marine Environment (PAME) Working Group. The activities of the Protection of the Arctic Marine Environment Working Group are governed by the Rules of Procedure of the Arctic Council. The following guidelines should be read in conjunction with the Rules of Procedure.